2021
DOI: 10.24953/turkjped.2021.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of immunity against Bordetella pertussis in pregnant women and an overview of the vaccination schedule in Turkey

Abstract: Background. Pertussis caused by Bordetella pertussis, is a disease leading to significant morbidity and mortality in neonates and infants. Direct protection of the infant may be achieved by maternal and neonatal vaccination. Despite primary vaccination, infants under six months pose the greatest risk of infection with pertussis. Maternal immunization provides a high level of infant protection from birth until immunity is achieved by active vaccination. There is no routine Tdap vaccination recommendation for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…10,11 While the coverage of the pertussis vaccine included in the NIP in Turkiye was 78% in 1991, it increased over the years and was found to be 98% in 2018. 12,13 However, in a study conducted in our country, it was observed that none of the 786 pregnant women evaluated did not receive pertussis vaccination. 14 In another study, the rate of those who wanted to have pertussis vaccination in case it was recommended during pregnancy was found to be 11.2%.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…10,11 While the coverage of the pertussis vaccine included in the NIP in Turkiye was 78% in 1991, it increased over the years and was found to be 98% in 2018. 12,13 However, in a study conducted in our country, it was observed that none of the 786 pregnant women evaluated did not receive pertussis vaccination. 14 In another study, the rate of those who wanted to have pertussis vaccination in case it was recommended during pregnancy was found to be 11.2%.…”
Section: Discussionmentioning
confidence: 89%
“…Anti-FHA may also be formed against other Bordetella species and other bacteria. 13 However, anti-FHA has been evaluated together with anti-PT in many studies. In Erik et al 20 study, when the threshold value for seronegativity was accepted as 10 IU/mL, anti-FHA level was found negative in 51.9% of pregnant women and 44.2% of cord blood.…”
Section: Discussionmentioning
confidence: 99%